Synthesis, physico-chemical and biological properties of DNA and RNA oligonucleotides containing short alkylamino internucleotide bond - Sobczak, Milena; Kubiak, Katarzyna; Janicka, Magdalena; Sierant, Malgorzata; Mikolajczyk, Barbara; Nawrot, Barbara (Collection of Czechoslovak Chemical Communications, 2011)
The condensation of the 5′-O-DMT-3′-deoxy-3′-aminothymidine with 3′-O-TBDMS-thymidine- 5′-aldehyde, followed by reduction of the resultant imine derivative and removal of tert-butyldimethylsilyl (TBDMS) protecting group, provided a dimer (denoted as TNHT), which is a congener of dithymidine phosphate with the phosphate linkage 3′-O-P(O)(OH)-O-5′ replaced with an amino group (–NH–). After phosphitylation of the 3′-OH group, the dimer TNHT was introduced (by the standard phosphoramidite approach) into a central part of the nonadecathymidylate. This oligomer exhibited lower affinity to the complementary single and double stranded DNA complements as compared to unmodified T19 oligonucleotide. The cleavage of modified oligomer with the snake venom and calf spleen phosphodiesterases was completely suppressed at the site of modification. RNA oligomers containing the TNHT dimer were used for preparation of siRNA molecules directed towards mRNA of BACE1 (beta-site amyloid precursor protein cleaving enzyme). The presence of the TNHT units at the 3′-ends of the RNA strands of the siRNA molecule (the siRNA itself is an effective gene expression inhibitor for BACE1) preserved the gene silencing activity and improved the stability of the modified siRNA in 10% fetal bovine serum.
Keywords: Schiff Bases; Chemistry, Clinical; DNA; thymidin; Oligonucleotides; klinická chemie; oligonukleotidy; RNA; Thymidine; Schiffovy báze